KAJI NUMERIK DAN EKSPERIMENTAL PERPINDAHAN PANAS PADA EVAPORATOR UNTUK MENDINGINKAN UDARA - Darmanto, Prihadi Setyo; Arjanto, Deddy Dwi; Ismail, Muhammad (Mesin, 2005)
This paper presents numerical and experimental study of heat transfer on fins-tube heat exchanger that functioned as an evaporator for coolingof humid air. In this case, change of phase occurred both on air and refrigerant. The proposed numerical analysis is based on the application of mass and energy balances implemented at small control volumes that were part of evaporator. The result of numerical evaluation was then compared to the experimental observation. A good agreement between experimental and numerical results was achieved and the proposed numerical method also could be used as a tool in designing fins tube heat exchanger with phase change in both fluids.